Stability-Indicating Forced Degradation Study of Thymoquinone Using RP-HPLC - Mayur Raval, Ishan Panchal (South Eastern European Journal of Public Health, 2025)
Thymoquinone (TQ), a bioactive compound derived from Nigella sativa, exhibits a range of therapeutic properties, but its chemical instability under various environmental conditions presents a challenge to its pharmaceutical formulation. This study aimed to evaluate the forced degradation behavior of Thymoquinone under different stress conditions, including hydrolytic, oxidative, thermal, and photolytic degradation. A stability-indicating reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated in accordance with ICH guidelines, assessing parameters such as specificity, linearity, precision, accuracy, and robustness. The method demonstrated excellent resolution and sensitivity, enabling the separation and quantification of Thymoquinone and its degradation products. Forced degradation studies revealed that Thymoquinone is most susceptible to thermal and oxidative degradation, with thermal conditions causing a significant degradation of 14.68% and oxidative stress resulting in a 5.25% degradation. Photolytic degradation led to a 12.11% reduction in Thymoquinone content, while acid and base hydrolysis caused minimal degradation (1.53% and 0.78%, respectively). The findings underscore the importance of optimizing storage, packaging, and formulation strategies to maintain Thymoquinone’s stability. The validated RP-HPLC method can be employed for routine quality control and stability testing of Thymoquinone-containing pharmaceutical products, ensuring regulatory compliance and product efficacy over its shelf life.